Relative Controllability of Linear Systems of Fractional Order with Delay - Henriquez-Miranda, H; Mur-Voigt, T (American Institute of Mathematical Sciences, 2015)
In this paper we are concerned with the controllability of control systems governed by a fractional differential equations with delay. Using the Mittag-Leffler function we dene the concept of solution, and applying the properties of the Laplace transform we characterize the relative or pointwise controllability of the system. Our results generalize those of Kirillova and Churakova, which were established for first order systems. Finally, we show that functionally controllable fractional systems are rare. © 2015, American Institute of Mathematical Sciences. All rights reserved.